Equivalent viscous damping of steel members for direct displacement based design. (October 2021) - Tarawneh, Ahmad; Majdalaweyh, Sereen; Dwairi, Hazim
Abstract: Predicting the required equivalent damping ratio is an essential step in predicting the structural element ductility demand through Direct Displacement Based Design methodology. This study presents an equivalent damping ratio model for steel members based on the bilinear hysteresis model with a post-yielding stiffness ratio of 2% and an initial damping ratio of 2%. The hysteresis model and its mechanical properties are derived from shaking table test results conducted in Japan in previous study. The equivalent damping ratio in this study was evaluated at post-yielding stiffness ratios of 2% and 3% as recommended by the experimental study. Where it is concluded that the difference between the selected post yielding stiffness ratios did not influence equivalent damping ratio. Additionally, this study evaluated the effect of near-field earthquake records with forward-directivity and fling-step effects. The results show that the equivalent damping ratio for fling-step records is significantly higher than the equivalent damping ratio obtained using other records. Also, the study evaluated the effect of earthquake duration on the equivalent damping ratio by investigating the duration effect of 25 real records. The duration was measured using different metrics. The result indicated that duration measured by uniform definition is positively correlated to the equivalent damping ratio and longer significant duration imposes higher ductility demand on the structure.